198k views
5 votes
What is the answer to this
23=x-13

User Sixthsense
by
4.7k points

2 Answers

0 votes
Simplifying
23 + -1x = 13

Solving
23 + -1x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + -1x = 13 + -23

Combine like terms: 23 + -23 = 0
0 + -1x = 13 + -23
-1x = 13 + -23

Combine like terms: 13 + -23 = -10
-1x = -10

Divide each side by '-1'.
x = 10

Simplifying
x = 10
User RowanX
by
4.9k points
3 votes

Answer: 23=x-13 <=> x=23+13 <=> x=36

what is your grade?